Antecedents of destination brand experience - Tarigan, Miska Irani; Lubis, Arlina Nurbaity; Rini, Endang Sulistya; Sembiring, Beby Karina Fawzeea (Goodwood Publishing, 2023)
Purpose: The tourism sector is the leading sector for Indonesia's foreign exchange earnings. The Indonesian government has established six National Tourism Strategy Areas, including Lake Toba, North Sumatra. Development in the Lake Toba tourist area has been carried out, but it does not automatically bring tourists to visit the Lake Toba Tourism Area. The researcher intended to know the factors of the tourist brand experience in Lake Toba. Therefore, this study aims to confirm the factors obtained from a literature study. Research methodology: The research methodology used is a qualitative study, namely Focus Group Discussion. Participants in the Focus Group Discussion are Government Representatives, Tour Guides, Travel Agencies, and domestic tourists' representatives. Results: The study results should add to the Tourist Self-expression as a new precursor to the destination brand experience. Limitation: The study did not involve hospitality and other relevant governments to gain a broader perspective. Contribution: The results of this study hope to contribute to references for tourism marketing. Keywords: Brand experience, Destination branding, Tourism marketing, Lake Toba